Pengaruh Program E-Samsat Dan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Daerah Jakarta Pusat - Clara Shinta Alverina; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to determine the effect of the e-Samsat and Mobile Samsat programs on taxpayer compliance in the Central Jakarta area. The research was conducted using quantitative methods at the Central Jakarta Samsat Office. The sample used in this study consisted of 105 respondents who were calculated based on the Hair formula with accidental sampling technique. Data were collected using a questionnaire and processed using SPSS Statistic 25. The results of this study indicate that the e-Samsat program has a positive effect on taxpayer compliance with a value of 3.064 and a significance value of 0.003. Mobile Samsat also has a significant effect on taxpayer compliance with a value of 8.573 and a significance value of 0.000. The results of the analysis of the coefficient of determination show that the e-Samsat and Mobile Samsat variables simultaneously have a positive and significant effect on Motor Vehicle Taxpayer Compliance in the Central Jakarta Region, with an R Square value of 0.488 or 48.8%, while the remaining 52.2% is the effect of other variables not examined in this study.